2020
DOI: 10.1103/physrevresearch.2.022068
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of the Higgs mode in transport through a normal-metal–superconductor junction

Abstract: A superconductor subject to electromagnetic irradiation in the terahertz range can show amplitude oscillations of its order parameter. However, coupling this so-called Higgs mode to the charge current is notoriously difficult. We propose to achieve such a coupling in a particle-hole-asymmetric configuration using a DC-voltagebiased normal-metal-superconductor tunnel junction. Using the quasiclassical Green's function formalism, we demonstrate three characteristic signatures of the Higgs mode: (i) The AC charge… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Signatures of the Higgs mode in the charge current of a superconductor-normal metal tunnel junction were reported in Ref. [23]. Superconductors can induce superconducting correlations in nearby nonsuperconducting materials via the proximity effect.…”
Section: Introductionmentioning
confidence: 80%
“…Signatures of the Higgs mode in the charge current of a superconductor-normal metal tunnel junction were reported in Ref. [23]. Superconductors can induce superconducting correlations in nearby nonsuperconducting materials via the proximity effect.…”
Section: Introductionmentioning
confidence: 80%
“…Irrespective of microscopic models of the Dynes formula, we can incorporates Γ into the quasiclassical formalism of the BCS theory (see e.g., Refs. [21,22,[38][39][40][41]). Also, microscopic derivations of the Dynes formula have been investigated [42,43].…”
Section: Introductionmentioning
confidence: 99%
“…Additional theoretical works have studied the Higgs mode in unconventional superconductors [22] as well as the interplay of Higgs and Leggett modes in multi-band superconductors [23,24]. Furthermore, the occurrence of Higgs mode in superconductor-normal metal junctions [25] and its signatures in transport properties have been analyzed [26]. Recent reviews on Higgs physics in superconductors can be found in Refs.…”
Section: Introductionmentioning
confidence: 99%